Fathers' participation in the HPV vaccination decision-making process doesn't increase parents' intention to make daughters get the vaccine. Issue 7 (2nd July 2020) - Egawa-Takata, Tomomi; Nakae, Ruriko; Shindo, Mariko; Miyoshi, Ai; Takiuchi, Tsuyoshi; Miyatake, Takashi; Kimura, Tadashi
ABSTRACT: Introduction: The HPV vaccination rate in Japan has been dismally low. Our previous survey work found that mothers in Japan, who have a strong influence over their daughters, often are receptive to the fathers' participation in the family's decision-making process about getting their daughter HPV vaccinated. Methods: We conducted a survey to investigate the nature of the influence of fathers' participation on the mother's decision-making process. From an internet survey panel, we selected a pool of 1, 499 eligible mothers who had 12–18 years old daughters. The mothers were randomized into three Groups. To the mothers in Group A, we gave an educational leaflet regarding HPV vaccination and a second leaflet which recommended that they talk with their husbands about the vaccination. To Group B, we gave only the educational leaflet. No leaflets were sent to Group C. A structured survey questionnaire was then distributed through the internet to the mothers. Results: In Groups A, B, and C, their intention to have their daughter receive the HPV vaccine was 21.6%, 20.7% and 8.2%, respectively. The percent of Group A mothers who thought their husband's opinion was important for when they made the decision was significantly higher (70%) than in Group B (56.6%) or Group C (47.1%). Conclusions: The fathers' participation in the mothers' decision-making does not increase the likelihood of HPV vaccination for their daughters. On the other hand, the educational leaflet proved to be effective for this cause.